On mechanics of deformation and crushing processes - Berka, L. (Проблемы прочности, 2008)
The mechanics of crushing and breaking of particles is one of the most intractable problems in materials science. The stressed states of processed materials are significantly inhomogeneous, and thus the deformation and disintegration mechanisms vary greatly. Two techniques have been developed for realizing these processes as a quasi-homogeneous transition. The device and method developed by Enikolopov transform a solid polymer spontaneously into powder. The same loading system is now used for obtaining fine-grained metals, similarly as when using the ECAP device developed by Valiev. Both techniques are now used for obtaining nanostructured materials. The common feature of both types of methods is the formation of new physical surfaces. These are particle-free oversurfaces or grain boundaries. The method requires a supply of energy in the form of mechanical work, and this is mostly done by simultaneous action of pressure and shear stress. The formation offree oversurfaces in stressed solid bodies is the subject offracture mechanics. The Griffith equation is employed to describe the problem.